Association between Level of Interleukin 10 and Biochemical Tests in Some Iraqi Diabetic Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: Diabetes mellitus (DM) can be defined as clinical syndrome or disturbance of  carbohydrates metabolism   characterized by hyperglycemia ,so diabetes is immunes dependent disease in which the changed patterns  of expression of  cytokine, anti-inflammatory factors as interleukin-10 play an essential role in  many infections. As well as, IL-10 has important main inhibitory cytokine against the work of inflammatory cytokines, as interleukin 12. Therefore, this  study was designed to evaluate the serum level of interleukin 10 and biochemical tests in Iraqi diabetic patients and controls [fasting blood sugar (FBS);urea; creatinine; triglyceride (T.G);  total cholesterol;  low density lipoprotein (LDL) ; high density lipoprotein (HDL);  as well as very low density lipoprotein  (VLDL). Interleukin 10 (IL10) serum level was measure by ELISA kit for both groups. This study was conducted from January-April 2018 in Specialist Center for Endocrinology and Diabetes in Baghdad government and correlates between IL10 concentration and biochemical tests in diabetic Iraqi patients. Results of current study showed a high incidence of  both diabetes types ( I&II) of in the age group 2 (  41-60) years old  as (NO.= 13, 11) and percentage as (17.3, 14.7)  %respectively, so, female(NO= 18 ,14) and percentage as (20.0, 18.7) %respectively had a higher prevalence of diabetes than male[12.0 ,12.0) and high incidence of  diabetes in female[20.0, 18.7] % more than male. Additionally, this study showed that creatinine; urea; F.B.S levels were higher (26.7;4.0,28.0]% in diabetic type I than diabetic type II as (20,0,24.0]% and compare to control as [17.3, 14.7 and 0)%.and increased levels of lipid profile as ( Total Cholesterol; triglyceride T.G ;  LDL ; HDL ;    and  VLDL ) in diabetic type I as (10 ; 16 ; 12 ;1 ; 20) % than in diabetic type II; as well as; IL-10 serum level was abnormal with creatinine levels in 35 patients as percentage 46.7%;  also IL-10 serum level was abnormal with  fasting blood sugar for  39 patients as percentage 52.0%;  whilst only 3 patients as 4.0% with abnormal urea levels as well as IL-10 level was abnormal with levels lipid profile as  ( Triglyceride T.G ; Total Cholesterol;  LDL , HDL and  VLDL)as ( 1.3; 25.3; 38.7 ; 26.7 and 22.7) % respectively. Based on these facts, it may be concluded that abnormal serum levels of IL-10 with biochemical tests can be considered as risk factors of diabetes.